Characteristics of Charcoal Briquettes from Rajumas Wood Saw Waste (Duabanga moluccana Blume.) with Comparison of Molass Adhesive Composition - Rosadi, M. Kudsi; Wulandari, Febriana Tri; Ningsih, Rima Vera (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Characteristics of Charcoal Briquettes from Rajumas Wood Saw Waste (Duabanga moluccana Blume.) with Comparison of Molass Adhesive Composition